Synthesis of rhamnosylated arginine glycopeptides and determination of the glycosidic linkage in bacterial elongation factor P. Issue 3 (20th December 2016) - Wang, Siyao; Corcilius, Leo; Sharp, Phillip P.; Rajkovic, Andrei; Ibba, Michael; Parker, Benjamin L.; Payne, Richard J.
Abstract : We describe the synthesis and incorporation of α- and β-configured rhamnosyl arginine cassettes into Pseudomonas aeruginosa elongation factor P-derived glycopeptides. These were used to unequivocally determine the native anomeric configuration of the rhamnose moiety in EF-P. Abstract : A new class of N-linked protein glycosylation – arginine rhamnosylation – has recently been discovered as a critical modification for the function of bacterial elongation factor P (EF-P). Herein, we describe the synthesis of suitably protected α- and β-rhamnosylated arginine amino acid "cassettes" that can be directly installed into rhamnosylated peptides. Preparation of a proteolytic fragment of Pseudomonas aeruginosa EF-P bearing both α- and β-rhamnosylated arginine enabled the unequivocal determination of the native glycosidic linkage to be α through 2D NMR and nano-UHPLC-tandem mass spectrometry studies.